Kidney function derangements during summer in ambulatory heart failure patients. (14th October 2021) - Spitaleri, G; Cediel, G; Santiago-Vacas, E; Codina, P; Domingo, M; Zamora, E; Santesmases, J; Diez-Quevedo, C; Troya, M; Boldo, M; Alonso, N; Gonzalez, B; et al.
Abstract: Background: Heart failure (HF) is characterized by alterations in kidney function that are associated with poor prognosis and can be related to the evolution of the disease or induced by medical treatment. High temperatures during summer may result in some degree of dehydration, especially in patients treated with diuretics, and may contribute to transient glomerular filtration rate (eGFR) reduction. Objective: To assess creatinine and eGFR changes during summer in ambulatory heart failure patients. Methods: Consecutive patients with HF admitted at our HF Clinic (Spain) from August 2001 to December 2020 were included. eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula. We included in the analysis creatinine and eGFR values that were assessed at planned visits only, discarding urgent renal function assessments. Creatinine and eGFR values were grouped according to the period of the year (summer [from June to September, both included] vs. the rest of the year). Changes in creatinine and eGFR between the rest of the year and summer for each patient were evaluated using paired samples t-test. Results: Out of 37360 creatinine and eGFR values, 25458 were included in the analysis for a total of 2423 patients (median number of observations for each patient: 8, IQR 4–15). Mean creatinine and eGFR were 1.4±1.0 mg/dl and 63.0±27.7 ml/min, respectively. Table 1 shows baseline patient characteristics. Creatinine increased significantly during summer (1.44±0.9 mg/dl vs. 1.48±1.1 mg/dl, p<0.001). Similarly, eGFR was lower in summer as compared to the rest of the year 60.6±25.4 ml/min vs. 59.4±26.0 ml/min, p<0.001. Conclusions: In ambulatory HF patients in a Mediterranean area, we found significant worsening of renal function during summer, likely related to an imbalance between water intake and fluid loss. To prevent summer-driven kidney stress, diuretic treatment should be carefully adjusted during the hottest months of the year. Funding Acknowledgement: Type of funding sources: None.